System Xc-pathway as a potential regulatory target in neurological disorders - Chen, Ying; Xiao, Wei; Qian, Chengli; Huang, Linshu; Lv, Jianghao; Wang, Zhuo; Luo, Yi (Frontiers in Pharmacology, 2026)
The System Xc-pathway is composed of the 12-transmembrane transporter protein SLC7A11 (xCT) and the single-channel transmembrane protein SLC3A2 (CD98hc). We detail the pathway’s characteristics and distribution within the central nervous system, as well as its canonical role in maintaining glutathione synthesis and inhibiting ferroptosis, and its emerging non-canonical functions in metabolic coupling and neuroimmunity. A core theme is the pathway’s context-dependent and often paradoxical role across major neurological disorders, including ischemic stroke, Alzheimer’s disease, multiple sclerosis, Parkinson’s disease, and amyotrophic lateral sclerosis. Critically, we analyze how pathological activation of N-methyl-D-aspartate receptors (NMDARs) can dysregulate System Xc-through mechanisms involving calcium overload, reactive oxygen species, and specific signaling axes (e.g., Nrf2, PP2A/AMPK/HMGB1), thereby exacerbating excitotoxicity and oxidative damage. Conversely, System Xc-dysfunction can further fuel NMDAR-mediated injury, creating vicious pathogenic cycles. This analysis reveals that System Xc-is not a unitary target but a dynamic node within a complex network. Consequently, effective therapeutic strategies must move beyond broad inhibition and instead aim for nuanced, cell-type-specific, and disease-stage-precise modulation. This approach will selectively correct the dysfunction of System Xc-while preserving its essential physiological roles. It presents both a significant challenge and a promising frontier for future neuroprotective drug development.